BUNGA BANK PERSPEKTIF AHLI TAFSIR (TELAAH KRITIS TERHADAP BUNGA SIMPANAN DAN BUNGA PINJAMAN PADA BANK KONVENSIONAL) - Sofi Faiqotul Hikmah (Jurnal Ekonomi Syariah Darussalam, 2024)
Today many people question the status of conventional bank interest (interest) in Islam, especially on conventional banks. Some scholars consider bank interest like usury, others do not. The word rib?, is mentioned about nine times in the Qur’an in several places, namely al-Rum (30): 39, al-Nis?’ (4): 160-161, li Imr?n (3): 130, and al- Baqarah (2): 275-280. All these verses show the prohibition of usury in all economic activities for sure (muhkam). However, when usury is connected with one part of the transaction in banking activities, such as bank interest, the commentators have different opinions, some prohibit it because there is an al-ziy?dah element, and some allow it because they consider bank interest not to be doubled (adl’?fan mudh?’afatan) and do not persecute. Through a thematic interpretation approach, this research will be carried out in depth to find the views of the al-Qur’an regarding bank interest, namely deposit bank interest and loan bank interest. This paper is carried out by dissecting the verses related to bank interest, interpreting them in tahlili, ijmali and comparing them with various related interpretations.